Determination of the Daily Rhythm of Cortisol in the Saliva of Women and Men - Ljubijankić, Nevzeta; Kučukalić, Elma; Ljubijankić, Sead (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2016)
Saliva provides a useful and noninvasive alternative to blood for many biomedical diagnostic assays. Recently, saliva has been used as a biological sample of choice for the monitoring of hormones and other clinically important biomolecules. The assessment of cortisol in saliva has proven to be a valid and reliable reflection of the respective unbound hormone in blood and is widely accepted and a frequently employed method. Due to several advantages over blood cortisol analysis (e.g., stress-free sampling, laboratory independence, lower costs) saliva cortisol assessment can be the method of choice in basic research and clinical environments. Synthesis and secretion of cortisol has the most obvious circadian rhythm in nature. The highest concentration of cortisol in extracellular fluids is in the morning hours and the lowest one in the evening. The object of this study was to determine and compare the daily fluctuations of cortisol in saliva by measuring cortisol levels in the saliva of healthy individuals daily in certain periods. Next step was to compare the values of the concentrations of cortisol in test subjects of different sexes and determine the benefits of analysis of cortisol in saliva.